2012
DOI: 10.1111/j.1526-4637.2012.01402.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional Anesthesia as Compared with General Anesthesia for Surgery in Geriatric Patients with Hip Fracture: Does It Decrease Morbidity, Mortality, and Health Care Costs? Results of a Single-Centered Study

Abstract: Introduction Hip fracture in geriatric patients has a substantial economic impact and represents a major cause of morbidity and mortality in this population. At our institution, a regional anesthesia program was instituted for patients undergoing surgery for hip fracture. This retrospective cohort review examines the effects of regional anesthesia (from mainly after July 2007) versus general anesthesia (mainly prior to July 2007) on morbidity, mortality and hospitalization costs. Methods This retrospective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
67
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 19 publications
3
67
1
2
Order By: Relevance
“…2,[4][5][6]8 We demonstrated the same result as in these previous studies, but the length of follow-up among our included studies reached six months in only one study and was less than three months in the others.…”
Section: Knee Surgerysupporting
confidence: 74%
See 1 more Smart Citation
“…2,[4][5][6]8 We demonstrated the same result as in these previous studies, but the length of follow-up among our included studies reached six months in only one study and was less than three months in the others.…”
Section: Knee Surgerysupporting
confidence: 74%
“…3 Neuraxial anesthesia is used routinely in orthopedic surgery, but there is controversy regarding the beneficial effects of this anesthetic technique, taking into consideration the length of follow-up and its correlation with mortality and postoperative morbidity. 4 Although some systematic reviews have analyzed neuraxial anesthesia for orthopedic surgery, the reviewers looked for the magnitude of the effect in a separated manner, without pooling knee, hip, femur and ankle results in a meta-analysis. Thus, controversy remains regarding the effectiveness and safety of neuraxial anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Regional anesthesia has been hypothesized to decrease postoperative complications by reducing sympathetic activation and inflammation, by preventing venous stasis, and by avoiding tracheal intubation and positive pressure ventilation [6][7][8] . However, to our knowledge, the influence of anesthesia type on clinical outcomes has not been studied with large clinical trials, and the investigations that have been done have produced conflicting results [9][10][11] . In 2006, Mauermann et al performed a meta-analysis of studies carried out from 1966 to 2005 and found lower rates of deep vein thrombosis and pulmonary embolism following total hip arthroplasties done with regional anesthesia compared with those done with general anesthesia 12 .…”
mentioning
confidence: 99%
“…Some studies have not shown benefits 9,10 , while others have demonstrated decreased blood loss, fewer respiratory complications, and a lower risk of thromboembolism with regional anesthesia 11,35,36 . In a recent retrospective analysis from the National Joint Registry for England and Wales of ninety-day mortality after total hip replacement, spinal anesthesia, but not epidural anesthesia, was associated with a lower mortality rate 5 .…”
mentioning
confidence: 99%
“…Furthermore, there are benefits to using neuraxial anesthesia during both the perioperative and postoperative periods. 2,6,25,26 There may have been some misclassification between anesthesia types in our study, but this is likely minimal since we confirmed the anesthesia type defined through the hospital records with the fee-for-service physician codes for epidural catheter insertion and excluded individuals who had a code that did not match with the anesthesia type variable. Another limitation is that we could not separate the use of epidural anesthesia from spinal anesthesia in this study; however, both epidural and spinal anesthesia should demonstrate a signal in the same direction, so this would not explain our lack of associations.…”
Section: Strengths and Limitationsmentioning
confidence: 86%